Novel Plant Regeneration and Transient Gene Expression in Catharanthus roseus (The All Results Journal, 2015)
Catharanthus roseus genetic transformation represents a real challenge due, in part, to the lack of regeneration capability and this species’ recalcitrance to genetic transformation. In the present work, we demonstrate the regeneration of C. roseus plants from hypocotyls and cotyledons, using specific growth regulator conditions. Plants derived from hypocotyls and cotyledons were successfully acclimated and grown in the greenhouse. Furthermore, C. roseus meristem tissues were shown to have high shoot regeneration potential under conditions optimised for cotyledon- and hypocotyl-derived shooting. Meristem tissues were therefore investigated as a genetic transformation targets using both Agrobacterium tumefaciens and A. rhizogenes. Although meristem-derived shoots transformed with A. tumefaciens harbouring a p35S GUSplus construct revealed transient GUS expression and protein accumulation, they were not amenable to selection even after two months on selection medium. Transformation of C. roseus meristem tissues with A. rhizogenes resulted in a typical hairy root phenotype, in which the adventitious root tissue strongly expressed the p35S GUSplus construct, as revealed by intense GUS staining.